2018
DOI: 10.14393/bj-v34n5a2018-39470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrogel use on soybean cultivation hydrical stress

Abstract: Among the agricultural production factors, the water deficit is one of the main reasons that limits soy production in Brazil. In order to mitigate losses due to water stress in the plants, hydrogels appear as soil water conditioners. They are polymers capable of absorbing large amounts of water and are being used as a viable alternative to improve the storage of water in areas of scarcity. Hydrogen concentrations between 14 and 18 kg ha-1 resulted in higher plant height, number of pods, one hundred grain mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
1
9
0
4
Order By: Relevance
“…It sticks to plant roots and increasing the water-holding capacity of soil, but when the soil moisture reduces as temperature rises, then hydrogels slowly release moisture back to the plants as it is needed (Wu et al, 2010). In this respect, many investigators found positive effect on growth characters of soybean plants when they were treated with some soil amendments such as hydrogel for plant height (Fidelis et al, 2018), biochar for leaf chlorophyll (Qian et al, 2019) and superabsorbent polymer for total dry matter (Yazdani et al, 2007) as compared with untreated plants.…”
Section: Root and Nodulation Charactersmentioning
confidence: 99%
“…It sticks to plant roots and increasing the water-holding capacity of soil, but when the soil moisture reduces as temperature rises, then hydrogels slowly release moisture back to the plants as it is needed (Wu et al, 2010). In this respect, many investigators found positive effect on growth characters of soybean plants when they were treated with some soil amendments such as hydrogel for plant height (Fidelis et al, 2018), biochar for leaf chlorophyll (Qian et al, 2019) and superabsorbent polymer for total dry matter (Yazdani et al, 2007) as compared with untreated plants.…”
Section: Root and Nodulation Charactersmentioning
confidence: 99%
“…Hydrogel effects on productivity, phenology, root attributes and soil moisture dynamics. Hydrogels have been used as water-retaining polymers in agriculture 2,6,16,25−27 since they can retain a great amount of water when incorporated in soil and release it slowly more or less matching with plant requirement leading to improved crop growth and yield under water-stressed conditions 43 . In the current study, the applied hydrogels exhibited a signi cant effect on soybean and wheat growth, especially under limited irrigation and rainfed conditions.…”
Section: Discussionmentioning
confidence: 99%
“…A signi cant (P ≤ 0.05) enhancement in soybean seed yield (6-25%) and wheat grain yield (3-15%) in P-hydrogel applied plots compared to no-hydrogel (control) and K-hydrogel applied plots were observed (Table 3). All the other parameters being constant, the increase in yield may be attributed to the extended availability of water to plants in the polymer treatments during periods of water stress 10,11,43 . Similarly, Jarvis and Davies 44 reported that the increased photosynthesis rate and leaf relative water content in plants under superabsorbent polymers would enhance growth under drought-stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For this study the soybean cultivar MonSoy 8644 was used with two sources of hydrogels and five concentrations of the products, in a total of totaling ten treatments. The experimental design was a randomized block design (DBC), with four replicates, in a 5x2 factorial scheme, with five product concentrations (0, 5, 10, 15 and 20 kg ha -1 ) and two hydrogel sources (Hydroplan and Polim-Agri), in the seedling line in soil during the planting, according to Lopes (2016) and Fidelis et al (2018).…”
Section: Methodsmentioning
confidence: 99%